Optimization of noise emission level in diesel engine with biodiesel application using response surface methodology - J. M., Zikri; M. S. M., Sani; Jaliliantabar, Farzad (Universiti Malaysia Pahang, 2024)
This study used biodiesel to run a single-cylinder direct-injection diesel engine. The palm oil methyl ester is blended in different ratios of up to 20% and tested with different engine speeds and loads for noise level measurement. Mathematical modeling was then developed to correlate responses obtained by the noise levels of the engine components to the factors, including engine speed, engine load, and biodiesel blending percentage. Finally, using the developed models, all the numeric factors were optimized. Modeling results indicated that the significance of factors could vary for the engine components, whereas in this study, the intake phase-related factors showed the significance of all factors. Meanwhile, the optimization results highlighted that the best solution with the highest desirability number to satisfy all the responses was the B20 fuel blend (20% biodiesel fuel and 80% diesel fuel blend by volume) with 1200 rpm of engine speed. In conclusion, the study's outcomes revealed that optimization should be considered in developing a new policy for using biofuel in internal combustion engines.